1959
DOI: 10.1017/s0021859600035620
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the skeleton of the sheep. III. The relationship between phosphorous intake and resorption and repair of the skeleton in pregnancy and lactation

Abstract: With Plates 1, 2 and 3 and Two Text-figures)In Part II of this series an experiment was described in which the amounts of mineral matter withdrawn from the skeleton during pregnancy and lactation and the proportion recovered during a subsequent dry period were determined (Benzie, Boyne, Dalgarno, Duckworth, Hill & Walker, 1956). Radiological observations of the skeletons were made, and these, together with the results of bone analyses were compared with changes in serum calcium values. The experiment reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
3

Year Published

1961
1961
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 6 publications
5
24
3
Order By: Relevance
“…This contrasts to the work by Benzie et al (1959) with lactating sheep, in which up to proportionally 0.4 of skeletal ash reserves were resorbed by mid-lactation with P-deficient diets. This study was not specificially designed to monitor changes in bone mineral content with stage of lactation, with the majority of bone samples removed from cows in late lactation.…”
Section: Cow Fertilitycontrasting
confidence: 60%
“…This contrasts to the work by Benzie et al (1959) with lactating sheep, in which up to proportionally 0.4 of skeletal ash reserves were resorbed by mid-lactation with P-deficient diets. This study was not specificially designed to monitor changes in bone mineral content with stage of lactation, with the majority of bone samples removed from cows in late lactation.…”
Section: Cow Fertilitycontrasting
confidence: 60%
“…These results that could be regarded as changes induced the the lactation stage are in accordance with the findings of Duckworth and Hill (1953), Benzie et al (1956Benzie et al ( ,1959, IIlek et al (1977). It can be concluded from the presented observations that the onset oflactation or its late stage induces the increased demineralization of the skeleton.…”
Section: Discussionsupporting
confidence: 92%
“…It has been suggested that these animals had depleted body reserves to their full extent and so accommodated the shortage of dietary P by reducing P in milk (Dixon and Coates, 2010). The amount of P that can be mobilised from bones is estimated to be up to 30% (Benzie et al, 1959;Little, 1983) of an animal that has undergone full P-repletion. A 400kg animal would be expected to have about 2.5-3kg P in bone reserves (Dixon and Coates, 2010) a 30% mobilisation would therefore be 750-900g P. In northern Australia, beef breeding females are normally required to lactate for 4 to 6 months.…”
Section: Deposition and Mobilisation Of Phosphorus Reserves In Breedimentioning
confidence: 99%
“…P h i l . -W h i t n e y D o l l e m o r e -4 1 0 1 4 8 8 6 The repletion of bones occurs when nutritional demand is lowered or quality is improved as demonstrated by Benzie et al (1959) using differences in ash content in sheep bones. Bortolussi et al (1999) found steers given high P diets deposited 7-17g P/day into body reserves even though the ME content of the diet was only sufficient for small amounts of growth.…”
Section: Deposition and Mobilisation Of Phosphorus Reserves In Breedimentioning
confidence: 99%
See 1 more Smart Citation